Proposal to disregard athletics world records prior to 2005: a radical and misjudged initiative - Edwards, A. M.; Jones, A. M.; Pyne, D. B. (British Journal of Sports Medicine, 2018)
The recent announcement that the European Athletics Council has proposed to disregard all athletics world records set prior to 2005 has caused considerable controversy and debate among the athletics community. It is a radical initiative with commendable aims to redress the consequences of past undetected doping violations that may have led to some of the least attainable world records. This proposal has now been put to the world governing body, the International Amateur Athletics Federation (IAAF), and its merits require discussion.